All quiet on the Kemalist front?. (May 2015) - Borovalı, Murat; Boyraz, Cemil
As a result of its failure to embrace the increasingly visible social and political diversity in the country, Kemalism, the founding ideology of modern Turkey, is currently facing its severest legitimacy crisis. Through interviews with representatives of leading voluntary Kemalist associations, this article inquires whether there are attempts to reinterpret the doctrine in order to offer an alternative, credible vision in harmony with the existing social, political and economic realities of Turkey.